The integration of visual images and angular illusions - Martišius , V. (Psichologija, 1981)
The hypothesis that one of the formation levels of images is the integration of images by orbits of translation, rotation and dilation groups enables us to explain angular illusions.
Keywords: the integration of visual images; angular illusions